The Life Story of a Resilient Underprivileged Youth: Motivation to Learn Soft Skills (Malaysian Journal of Learning and Instruction, 2018)
Purpose â€“ The study explored how an underprivileged blind individual from an extremely poor family developed resilience and soft skills to thrive in life, despite challenges that could have easily hindered the development of his abilities.Methodology â€“ This qualitative study employed the narrative inquiry method, involving responsive interviews. Experiences over a period of time were retrospectively documented via the collection of a life story from one participant who was very distinctive to the phenomenon being studied. Data analysis was carried out manually using open, thematic and longitudinal coding methods, after which interpretation was done to provide meaning to the results. Findings â€“ Positive youth development in the participantâ€™s life may be the result of the ecological system he grew up in, supported by three synergistic protective factors: religiosity and spirituality, parental discipline, and care and support, in addition to the traumatic life turning points he experienced. Significance â€“ The findings provide directions for further research on the underprivileged in the Malaysian context. They would also be able to guide the government and other interested stakeholders on potential methods and initiatives to build resilience and motivation to learn soft skills so that underprivileged children will be able to thrive in life.